Модифицирующее влияние импульсных высоковольтных разрядов на активность растворов поверхностно-активных веществ - Сизоненко, Ольга Николаевна; Тафтай, Эдуард Иванович; Малая, Р. И.; Торпаков, Андрей Сергеевич; Липян, Евгений Васильевич; Колмогорова, Р. П. (НТУ "ХПИ", 2009)
Наведено результати комплексних досліджень дії електричних імпульсних високовольтних розрядів на колоїдні розчини поверхнево-активних речовин. Встановлені закономірності зв’язку процесів адгезії за участю поверхнево-активних речовин з максимумом тиску у каналі розряду.

Тhe results of complex researches of action of electric impulsive high-voltage digits on colloid solu-tions of superficially-active matters are given. Conformities to the law of communication of processes of adhesion with participation of superficially-active matters with maximum of pressure into the dis-charge channel are found.
Keywords: разрядный контур; запасаемая энергия; омический коаксиальный шунт; гидродинамические характеристики; коллоидные растворы